Forests of Himachal Pradesh and their Management - Chopra, R. S. (Indian Forester, 1959)
The note describes the forests of Himachal Pradesh giving their extent, classification, types, methods of management and exploitation. Forest administration, forestry problems, development plans and future prospects are also discussed. Briefly the forests in Himachal Pradesh cover an area of 3587 sq. miles or 33 per cent of the land area. They form the main source of revenue to the State and are of national importance for supply of timber to meet public requirements and on account of of thier role in protecting watersheds of important rivers in northern India. About 50 per cent of the forest area is under regular Working Plans. Coniferous timber, resin from chil pine, grasses and medicinal herbs are the chief forest products. The forests produced a gross revenue of Rs. 135 lakhs and a net surplus of Rs. 93 lakhs in 1957-58, besides meeting the requirements of local right-holders to the estimated value of Rs. 24.42 lakhs. An area of about 1100 sq. miles is potentially merchantable at present. Forests forms an asset of great potential value and offer a great scope for development. A big task lies ahead in the demarcation and reclothing of a million acres of degraded forests and waste-lands, development of communications for exploitation of hitherto unmerchantable areas and preparation of Working Plans.